IMPACT OF IN-WORK BENEFITS ON WORK INCENTIVES IN CROATIA: A MICROSIMULATION ANALYSIS (The South East European Journal of Economics and Business, 2024)
Generous social benefit systems reduce work incentives, which has prompted more than half of the EU countries to introduce some sort of make work pay policies. Previous research for Croatia has shown that certain types of households have very low work incentives. Therefore, this paper aims to analyse the impact of in-work benefits on work incentives of non-employed persons and the poverty rate in Croatia. Using the tax-benefit microsimulation model EUROMOD, which is based on the EU-SILC 2020 data, three hypothetical types of in-work benefits are simulated. The results show that the characteristics and the design of in-work benefits are essential, and the choice of the appropriate type of benefit depends on the policy objectives. This paper is the first to analyze the impact of in-work benefits on the work incentives of all non-employed persons in Croatia.